Foxfire 7 - 4 0 16; Gillespie, Paul F.; 5 (Garden City, NY : Anchor/Doubleday, 1982)
On cover: Ministers, church members, revivals, baptisms, shaped-note and gospel singing, faith healing, camp meetings, footwashing, snake handling, and other traditions of mountain religious heritage.
Wilson's Senior High School;Wilson's Public Library;Booklist
Adult;Adult.
Keywords: 2 -- 0; 6; Church history;Country life;Christianity.;Country life;Christianity.;Church history. -- United States.;Appalachian region.;Appalachian region; 20; 2